DINAMIKA POLITIK PENERAPAN KEBIJAKAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RSUD TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Yeri Wahyudi; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research entitled "The Political Dynamics of Implementation of Social Security Administering Agency (BPJS) at Kuantan Bay District General Hospital of Kuantan Singingi Regency". This research is based on Law Number 40 Year 2004 regarding National Social Security System (UU SJSN) which has been revised with Law No. 40 of Law Number 24 Year 2011 on Social Security Administering Board (UU BPJS). The formulation of the problem in this study is Who Any Actors Involved In Implementation Program Social Security Administering Agency (BPJS) At Teluk Kuantan Hospital and what are the interests of each of the actors or political actors. The problems that exist in this research is to see the political dynamics of the actors that took place at Kuantan Bay District General Hospital Kuantan Singingi Regency and wanted to see what the interests of the actors. The method used in this study is a qualitative method that describes the data descriptively. Data collection techniques used were in-depth interviews, documentation and observation, while other required data came from research informants and supported by supporting documents related to this research.Based on the results of research that has been done there are several findings, namely hospitals that have not the status of Regional Public Service Agency (BLUD) so that the required budget must be submitted first to the Local Government. While the local government together with the holding of elections simultaneously not focused on budget preparation, this can be said because of the low political will the executive and legislative support partner pair number 1 in drafting the budget quickly so that the budget is not properly set allocation which then arise the problem of deficiency Funds in the implementation of health services at Teluk Kuantan Hospital for BPJS health users.Keyword: Political Dynamics, Actors, BPJS